Autonomous Coastal Land Cover Assessment Using Polarimetric Decomposition of SAR Data - Bambang H. Trisasongko (Institute for Research and Community Services, Institut Teknologi Bandung, 2011)
The paper reports an experiment on classification using fully polarimetric SAR data. Many reports have been presented mentioning test sites in temperate regions utilizing polarimetric SAR data from airborne and/or spaceborne SAR sensors. However, few studies are dedicated to tropical region which highly dynamic land uses are observed. Using the AirSAR Sungai Wain fully polarimetric data, capability to extract features in coastal region has been demonstrated by an unsupervised classification technique fed by the CloudePottier decomposition theorem.